Shipping yield management model for liner shipping - Cheng, Meifeng. (2008)
Yield management is commonly used in transportation and service industries, particularly in the airlines and hotels. With the immense profitable results that brought to the companies employing yield management, it is worth a study on its implementation on the shipping industry as well. With the upsurge of containerisation and liner services, yield management appears most viable in the liner shipping industry. This holds especially true when competition continues to soar and many alliances and M&A are taking place in liner industry. As such, the employment of yield management model in liner companies may opt for operational or management improvements within the company whilst strategic alliance is viewed as an option of enhancing portfolio rather than yield generation.